Analysis of the Influence of Product Quality, Facility Quality, and Service Quality on Consumer Purchase Intention in Coffee Shops in Serang City - Lusinto, Widodo Hari; Prasetya, Muhammad Hanafi Indra (Dinasti International Journal of Management Science, 2026)
The growth of the coffee shop industry in Serang City has increased significantly in line with the urban lifestyle that positions coffee as an essential part of social and professional activities. However, not all coffee shops can sustain their competitiveness, making it important to analyze the factors influencing consumers’ purchase intention. This study aims to examine the effect of product quality, facility quality, and service quality on consumers’ purchase intention toward coffee shops in Serang City, both partially and simultaneously. The research employed a quantitative approach using a survey method involving 96 respondents. Data were analyzed using multiple linear regression with the aid of SPSS software. The findings reveal that product quality, facility quality, and service quality each have a positive and significant effect on purchase intention, with a combined contribution of 73.6%. These results emphasize that enhancing product quality, providing comfortable facilities, and delivering friendly and professional service are key factors that shape consumer attraction, loyalty, and purchasing decisions in coffee shops across Serang City.